2009
DOI: 10.1590/s0103-64402009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implants placed into infected sockets: a case report with 3-year follow-up

Abstract: The esthetics and functional integrity of the periodontal tissue may be compromised by dental loss. Immediate implants became a viable option to maintain the periodontal architecture because of their anatomic compatibility with the dental socket and the possibility of eliminating local contamination. This article describes the procedure of immediate implant placement in the anterior maxilla replacing teeth with chronic periapical lesions, which were condemned due to endodontic lesions persisting after failed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
0
30
0
1
Order By: Relevance
“…Many studies have investigated immediate implant placement in infected extraction sockets due to periapical lesions 5,12,13,17,20,24,31,32,35,55) . Few have investigated the potential adjunctive effect of concomitant use of PRF and DFDBA bone grafts in such cases, however, which was, therefore, the purpose of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated immediate implant placement in infected extraction sockets due to periapical lesions 5,12,13,17,20,24,31,32,35,55) . Few have investigated the potential adjunctive effect of concomitant use of PRF and DFDBA bone grafts in such cases, however, which was, therefore, the purpose of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of implant failure has been reported in sockets with periapical lesions, especially with placement of machined-surface implants 5) . Moreover, many studies have reported an increase in loss of endosseous implants at sites associated with periodontal disease 12,24,35) , whereas few have reported satisfactory results 13,20) . Similar success rates have been reported, however, with immediate implant placement whether the site was infected or not, provided infection was controlled thorough debridement of alveolar tissue by curettage and administration of broad-spectrum antibiotics 17,20,31,32,50,55) .…”
Section: Introductionmentioning
confidence: 99%
“…However, periapical pathology can be contraindica ons for placing the implants without 6,7 regression of the lesions. Some authors claim success even [8][9][10][11] in such condi ons with proper debridement and care. Thus immediate implant placement has less contraindica ons in modern era of den stry.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of the articles were excluded as they had no IOPAs of the lesion. 7,11,24,25,33,35,[37][38][39]45,48,53 A total of 54 IOPAs from 36 articles were compiled. One periodontist (SR) and one implantologist (TAB) independently analyzed the IOPAs.…”
Section: Literature Searchmentioning
confidence: 99%